Thinking – feeling: the conceptual landscape of R. G. Collingwood's "the principles of art" - Ternova, Maryna (Ukrainian Cultural Studies, 2024)
Background. The theoretical field of the English philosopher, historian of science, and art theorist Robin George Collingwood (1889-1943) covers a wide range of problems. The article deals specifically with the phenomenon of "thinking – feeling", which requires actualization and clear delineation due to the current increasing attention to the tendencies in the development of various culture-making models. Methods. The author uses uses the potential of the chronological (principles of historicism), analytical and systemic methods (in anatomizing and synthesizing the development of historical and cultural stages), and comparative (in comparison of theoretical conclusions) methods, as well as the principles of the cultural studies approach (interdisciplinarity, personalization, dialogism). Results. Since the understanding of the nature of both "thinking" and "feeling" has a long and controversial history, it is important to reconstruct all its components, among which the concept of "thinking-feeling" proposed by R.G. Collingwood occupies a prominent place. The article presents both the position of the English philosopher and the general for Ukrainian humanities theoretical interpretation of thinking and feeling, and also the results of the comparative analysis of R.G. Collingwood's views and the orientations of contemporary philosophers, cultural critics, and art historians. Considering that R.G. Collingwood created the "thinking-feeling" concept to support the understanding of a wide problematic field related to artistic creativity, art history, and trends in its development in the first decades of the XX century, the article uses the formal-logical structure of "conceptual landscape" to identify and analyze his theoretical guidelines. In this context, R.G. Collingwood's attitude towards English Romanticism, which gave the world a number of outstanding poets, is of particular importance. While writing "The Principles of Art", English scientist was concerned with developing new models for the study of artistic thinking as the exhaustion of Romanticism was becoming apparent at that time. Conclusions. Given that the "conceptual landscape" is a structure that determines scientific novelty, the article stresses the need for a theoretical attribution of the concepts of "thinking" and "feeling" in "The Principles of Art" art-historical dimension. Сomprehensiveness of R.G. Collingwood's study meets the requirements of an interdisciplinary approach, one of the cornerstones of cultural analysis.
Keywords: thinking-feeling; conceptual landscape; contrast; neutered feelings